Split Frame Thinking and Multiple Scenario Awareness: How boys’ game expertise reshapes possible structures of sense in a digital world. - Cross, Beth (Discourse: Studies in the Cultural Politics of Education, 2005)
This article takes a detailed look at how a group of 10-year-old boys mutually construct an evolving multilinear scenario whilst playing a storytelling game in class, borrowing from a number of genres and forms of engagement in ICT-mediated popular culture to perform for each other in patterns which defy linear description or analysis. Their playful production challenges standard means of representing and analysing transcript, necessitating a paradigm shift to a more visual form of discourse mapping. This visual method of analysis is drawn from complexity theory and fractal geometry. The article uses this analysis to raise questions about the criteria which teachers use to assess language competence as ICT-mediated popular culture continues to powerfully reconfigure the language context surrounding schools, (Buckingham, 2000). In conclusion, the article reflects on the consequences for both teachers and children's learning identities and practices.